2018
DOI: 10.1093/jxb/ery159
|View full text |Cite
|
Sign up to set email alerts
|

Redefining nitric oxide production in legume nodules through complementary insights from electron paramagnetic resonance spectroscopy and specific fluorescent probes

Abstract: The combined use of EPR spectroscopy and the specific fluorescent dye 4,5-diaminofluorescein diacetate uncovers sites of nitric oxide production in legume nodules and warns of potential artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…However, additional forms of Lb have been detected under certain developmental or stressful conditions. The presence of nitrosyl‐Lb in soybean intact nodules was reported using electron paramagnetic resonance in healthy nodules (Mathieu et al , ) and in nodules deficient in the bacteroid denitrification enzymes NirK or Nor (Calvo‐Begueria et al , ), especially in response to flooding conditions (Sánchez et al , ). On the other hand, green pigments derived from Lbs were observed in senescing soybean nodules (Jun et al , ,b) and almost 20 years later identified as nitri‐Lbs, unveiling the generation of nitrating reactive compounds in nodules (Navascués et al , ).…”
Section: Globins In Symbiosismentioning
confidence: 92%
“…However, additional forms of Lb have been detected under certain developmental or stressful conditions. The presence of nitrosyl‐Lb in soybean intact nodules was reported using electron paramagnetic resonance in healthy nodules (Mathieu et al , ) and in nodules deficient in the bacteroid denitrification enzymes NirK or Nor (Calvo‐Begueria et al , ), especially in response to flooding conditions (Sánchez et al , ). On the other hand, green pigments derived from Lbs were observed in senescing soybean nodules (Jun et al , ,b) and almost 20 years later identified as nitri‐Lbs, unveiling the generation of nitrating reactive compounds in nodules (Navascués et al , ).…”
Section: Globins In Symbiosismentioning
confidence: 92%
“…NO production also has been reported in mature N 2 -fixing nodules, especially in infected rhizobia-harbouring cells (Calvo-Begueria et al, 2018;Horchani et al, 2011) and during nodule senescence (Cam et al, 2012;Fukudome et al, 2019). Accumulating evidence also supports a multifaceted role for NO during N 2 -fixation.…”
Section: Nitric Oxide Plays Pivotal Roles During Pathogen Defence Amentioning
confidence: 63%
“…NO binds to the Fe 2+ of leghemoglobin and forms an Lb 2+ NO nitrosyl complex (left). Calvo-Begueria et al (2018) have demonstrated that this complex can be detected by EPR spectroscopy in intact soybean nodules, allowing a direct monitoring of NO production. Nodules containing Lb 2+ NO show spectra with a clear diagnostic signal in the range of 320–345 mT (right; see Calvo-Begueria et al , 2018 ).…”
Section: Breakthrough Methodologymentioning
confidence: 99%
“…The paper presented by Laura Calvo-Begueria and colleagues describes a method that enables detection of NO in vivo ( Calvo-Begueria et al , 2018 ). They investigated the formation of the nitrosyl–leghemoglobin complex (Lb 2+ NO) and the production of NO in legume nodules using EPR spectroscopy and the fluorescent specific dye 4,5-diaminofluorescein diacetate (DAF-2 DA), respectively.…”
Section: Breakthrough Methodologymentioning
confidence: 99%